Actical Errors in Surgical Treatment of Strengthened Abdominal Hernias - Rayimov G.N; Tillaboldiyev A.R; Saloxiddinov N.; Dekhkonov Sh.Sh (Peerian Journals Publishing, 2022)
The study of literature data on the issue of strangulated abdominal hernias suggests that the problem of surgical treatment of this category of patients has not lost its relevance to the present, primarily due to the significant incidence of this disease, the frequency of diagnostic errors in this disease does not tend to decrease. The main causes of errors in diagnosis and tactics are seen in such factors as the late admission of patients to the hospital, especially in elderly and senile patients, the erasure of symptoms in these patients and the presence of a large number of concomitant diseases that complicate diagnosis and aggravate the postoperative period. Unfortunately, there are also frequent cases of careless, inattentive examination of patients by doctors, both before the hospital and the hospital network, leading to a review of the pathology, or to an incorrect interpretation of the data obtained.
Keywords: pathology; Unfortunately; disease; significant